Promoting physical activity and academic achievement through physically active learning: Qualitative perspectives of co-design and implementation processes. - Laurie Simard; Julie Bouchard; Martin Lavallière; Tommy Chevrette (PLoS ONE, 2023)
This article discussed the issue of low PA levels among school-aged children and highlights the promising approach of school-based interventions, including physically active learning (PAL), to increase PA levels. The study aimed to co-design and to assess the implementation of a PAL program for 8 weeks in 4 elementary classrooms (82 students and 7 teachers), emphasizing the potential of integrating PA with academic learning and the importance of co-designing programs with teachers to maximize their effectiveness. Technology was found to support PAL practices in promoting PA and academic achievement. The study underscores the need for further research to explore the societal implications of PAL programs, including their potential to improve the health and well-being of children while promoting positive academic outcomes.